2024
DOI: 10.3389/fmars.2024.1334937
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulators improve the growth and physiology of transplanted Thalassia Hemprichii fragments

Zhaoyang Li,
Yunfeng Shi,
Muqiu Zhao
et al.

Abstract: IntroductionThe transplantation of seagrass fragments with shoots and rhizomes is the most common method for the ecological restoration of damaged seagrass meadows.MethodsThe aim of this study was to explore the effects of exogenous addition (10 mg per month for 3 months) of three commonly used plant growth regulators (PGRs), including indoleacetic acid (IAA), gibberellin (GA3), and paclobutrazol (PP333) on the growth and physiology of transplanted Thalassia hemprichii fragments (TTFs), with and without the rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Root vigor is an important physiological indicator of plant growth robustness and stress resistance, 51 and this study showed that using IAA soaking and applying exogenous melatonin could significantly improve the root vigor of three desert plants. Zhaoyang Li et al 52 found that treatment significantly improved root viability in Thalassia Hemprichii using the IAA component compared to the CK group. These results indicated that IAA played a promoting role in improving root viability.…”
Section: Disscussionmentioning
confidence: 99%
“…Root vigor is an important physiological indicator of plant growth robustness and stress resistance, 51 and this study showed that using IAA soaking and applying exogenous melatonin could significantly improve the root vigor of three desert plants. Zhaoyang Li et al 52 found that treatment significantly improved root viability in Thalassia Hemprichii using the IAA component compared to the CK group. These results indicated that IAA played a promoting role in improving root viability.…”
Section: Disscussionmentioning
confidence: 99%